Using Videos to Increase Midwifery Students Listening Skills and Students’ Attitude - Silvia, Resi (Kopertis Wilayah X (Sumbar, Riau, Jambi, dan Riau Kepulauan), 2018)
Video materials were used this study to examine the effectiveness of teaching English and to evaluate university students’ attitudes towards the use of video materials in teaching listening skills. The population for this study was 32 first-year midwifery students in the second semester of the academic year 2016/2017 at Adiwangsa University, Jambi. The sample were selected by total sampling technique. The study was conducted in 12 meeting including pretest and posttest. The one-group pretest-posttest design was implemented in this study. The instruments used in this study were lesson plans, English comprehension tests (pretest and posttest) and a questionnaire of the students’ attitude. Regarding the data analysis, mean score and pretest-posttest scores for the dependent sample were employed. The result indicated that the midwifery students’ English listening comprehension ability increased significantly after learning with videos and midwifery students had positive attitudes towards using videos in teaching listening skills.